Perspektif Visual dan Interaksi nilai Budaya di Situs Pokekea - Marutama, I Gusti Ngurah Tri; Setyawan, Alfan; Yudhanto, Sigied Himawan (Universitas Mercu Buana, 2024)
Pokekea site, located in the Besoa Valley of Lore Lindu National Park in Central Sulawesi, Indonesia, is a megalithic site rich in cultural and historical artifacts. This study aims to examine how visual perspectives and cultural interactions at the Pokekea site have influenced changes in the values and identity of local life. A qualitative method with a cultural anthropology approach was used to observe and analyze the changes in visual and cultural aspects that occurred by collecting data through discussion, participatory observation, and document study. The results showed that visual perspectives and cultural value interactions have caused a shift in values and identity at the Pokekea megalithic site in Besoa Valley. Traditional values that are local and communitarian have led to formal values that are global. The visual perspective is seen in the aesthetic function of megalithic objects as inanimate objects that tend to be more open to change and innovation and are more easily influenced by outside cultures, which, of course, the interaction of cultural values will be a strategic effort to maintain a balance between the preservation of traditional culture and adaptation to changing times.